The Responses of Malaysian Public Listed Companies to the IFRS Convergence - Phang, Soon Yeow; Mahzan, Nurmazilah (Asian Journal of Business and Accounting, 2017)
As the Financial Reporting Foundation (FRF) and Malaysian Accounting Standard Board (MASB) announced their plan to bring Malaysia to full International Financial Reporting Standards (IFRS) convergence by 1 January 2012, it is envisaged that Malaysian public listed companies will be prepared for the IFRS convergence. Our study was carried out during the peak of the convergence preparation in Malaysia. We aim to identify external drivers that influence the preparedness of companies for IFRS convergence by applying institutional theory perspectives as well as examine internal barriers that may impede the implementation of IFRS through the lens of a resource-based view. Of 859 questionnaires sent out, a total of the 150 responses were used in the data analysis of this study contributing a usable response rate of 17.46%. The general results show that respondents are prepared for the IFRS convergence. Our findings specifically reveal that the majority of respondents agree that coercive forces from stakeholders, especially regulatory forces influence their preparedness to implement IFRS. Additionally, this study points to the important roles of national accounting regulators and external auditors in influencing the degree of preparedness for IFRS convergence. The findings further demonstrate that it is not an easy task to implement IFRS and hence proper preparatory actions taken by companies are necessary in the convergence process. Overall, this study contributes to the research study’s gap of limited exploration study on the IFRS adoption at organisation field from institutional theory perspectives, as previous institutional research focused on isomorphism influence on the IFRS adoption at the national level perspectives. Further, this study uses a resource-based view to explore the responses of companies for full convergence with IFRS. Hence, this study contributes to literature on IFRS adoption by offering insights into the internal barriers faced by companies in the IFRS convergence process. From a practical standpoint, this study provides several implications for accounting regulators, standard setters, external auditors and Malaysian public listed companies.